Principal component analysis of summertime ground site measurements in the Athabasca oil sands with a focus on analytically unresolved intermediate-volatility organic compounds - Tokarek, Travis W.; Odame-Ankrah, Charles A.; Huo, Jennifer A.; McLaren, Robert; Lee, Alex K. Y.; Adam, Max G.; Willis, Megan D.; Abbatt, Jonathan P. D.; Mihele, Cristian; Darlington, Andrea; Mittermeier, Richard L.; Strawbridge, Kevin; et al. (ATMOSPHERIC CHEMISTRY AND PHYSICS, 2018)
In this paper, measurements of air pollutants made at a ground site near Fort McKay in the Athabasca oil sands region as part of a multi-platform campaign in the summer of 2013 are presented. The observations included measurements of selected volatile organic compounds (VOCs) by a gas chromatograph-ion trap mass spectrometer (GC-ITMS). This instrument observed a large, analytically unresolved hydrocarbon peak (with a retention index between 1100 and 1700) associated with intermediate-volatility organic compounds (IVOCs). However, the activities or processes that contribute to the release of these IVOCs in the oil sands region remain unclear. Principal component analysis (PCA) with varimax rotation was applied to elucidate major source types impacting the sampling site in the summer of 2013. The analysis included 28 variables, including concentrations of total odd nitrogen (NOy), carbon dioxide (CO2), methane (CH4), ammonia (NH3), carbon monoxide (CO), sulfur dioxide (SO2), total reduced-sulfur compounds (TRSs), speciated monoterpenes (including alpha- and beta-pinene and limonene), particle volume calculated from measured size distributions of particles less than 10 and 1 mu m in diameter (PM10-1 and PM1), particle-surface-bound polycyclic aromatic hydrocarbons (pPAHs), and aerosol mass spectrometer composition measurements, including refractory black carbon (rBC) and organic aerosol components. The PCA was complemented by bivariate polar plots showing the joint wind speed and direction dependence of air pollutant concentrations to illustrate the spatial distribution of sources in the area. Using the 95% cumulative percentage of variance criterion, 10 components were identified and categorized by source type. These included emissions by wet tailing ponds, vegetation, open pit mining operations, upgrader facilities, and surface dust. Three components correlated with IVOCs, with the largest associated with surface mining and likely caused by the unearthing and processing of raw bitumen.